Graphene: The Exfoliation of Graphene in Liquids by Electrochemical, Chemical, and Sonication‐Assisted Techniques: A Nanoscale Study (Adv. Funct. Mater. 37/2013). (1st October 2013) - Xia, Zhen Yuan; Pezzini, Sergio; Treossi, Emanuele; Giambastiani, Giuliano; Corticelli, Franco; Morandi, Vittorio; Zanelli, Alberto; Bellani, Vittorio; Palermo, Vincenzo
<x xml:space="preserve">Abstract</x> A graphite 'flower' is produced by V. Palermo and co‐workers in order to study the production and exfoliation mechanism of soluble of graphene and graphene oxide nanosheets due to chemical etching, electrochemical treatment, or sonication in organic solvents of bulk graphite. In the background of the back cover image, the same material is visualized by electron microscopy. The exfoliation process and roughening of the flat graphite substrate upon exfoliation is directly visualized at the nanoscale on page 4684. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>